2011
DOI: 10.4049/jimmunol.1002256
|View full text |Cite
|
Sign up to set email alerts
|

An Intact Canonical NF-κB Pathway Is Required for Inflammatory Gene Expression in Response to Hypoxia

Abstract: Hypoxia is a feature of the microenvironment in a number of chronic inflammatory conditions due to increased metabolic activity and disrupted perfusion at the inflamed site. Hypoxia contributes to inflammation through the regulation of gene expression via key oxygen-sensitive transcriptional regulators including the hypoxia-inducible factor (HIF) and NF-κB. Recent studies have revealed a high degree of interdependence between HIF and NF-κB signaling; however, the relative contribution of each to hypoxia-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 25 publications
5
111
2
Order By: Relevance
“…Chronic inflammation also contributes to the local deficiency of oxygen due to the combination of reduced circulation at inflammatory sites and increased metabolic demand from infiltrating immune cells. In a feed-forward manner, hypoxia can promote chronic inflammation and thus, itself, in the developing TME through activation of NF-κB signaling in macrophages, neutrophils and non-immune cells, a finding recently confirmed in vivo in the lungs of mice [65,66].…”
Section: Inflammation Creates a Hypoxic Microenvironmentmentioning
confidence: 74%
“…Chronic inflammation also contributes to the local deficiency of oxygen due to the combination of reduced circulation at inflammatory sites and increased metabolic demand from infiltrating immune cells. In a feed-forward manner, hypoxia can promote chronic inflammation and thus, itself, in the developing TME through activation of NF-κB signaling in macrophages, neutrophils and non-immune cells, a finding recently confirmed in vivo in the lungs of mice [65,66].…”
Section: Inflammation Creates a Hypoxic Microenvironmentmentioning
confidence: 74%
“…IL-1), inhibition of the prolyl-4-hydroxylases blocks NF-B activity suggesting a stimulus and/or cell type-specific 14 interaction between HIF and NF-B pathway [92]. Once active, NF-B induces HIF-1 via evolutionary conserved consensus binding sites identified in the HIF-1 promoter [91,[93][94][95]. Since NF-B activity is not sufficient for the accumulation of the HIF-1 protein in the absence of hypoxia, current data suggest that the canonical NF-B pathway contributes to the maintenance of the HIF-1mRNA level, a pre-requisite of the PHD-mediated posttranslational regulation of the HIF system [91].…”
Section: Crosstalk With Nf-kappabmentioning
confidence: 99%
“…This creates a situation whereby both the hypoxic signalling pathway, through the Hypoxia Inducible factor (HIF), and the inflammatory signalling pathway, through Nuclear factor-!B (NF!B), are activated. Recent studies have shown that hypoxia influences the NF!B pathway and that HIF may play an important role in inflammation [4][5][6][7][8]. However, the relative contributions of HIF and NF!B into creating transcriptional activation profiles leading to a coordinated regulation of hypoxia-induced inflammatory gene expression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its role as a master regulator of immunity and inflammation, its transcriptional activity and regulatory pathway have been an area of intense research [12]. Substantial evidence now exists that hypoxia can activate NF!B in vivo [8,13] and in vitro [5,7,8,14]. While the exact mechanism involved in the activation of NF!B remains to be fully elucidated, recent evidence has suggested that the same oxygen sensing enzymes, which confer oxygen sensitivity to the HIF pathway also play a role in activation of NF!B in response to hypoxia [5,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation